The Filipina as Artist and Art Subject in 19th Century Philippine Art - Icagasi, Rosa Maria Magno (Review of Women's Studies; Vol 8 No 2 (1998): Review of Women's Studies Volume VIII, Number 2 (July-December 1998))
---